2021
DOI: 10.3389/fsurg.2021.779571
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Meta-Analysis of the Efficacy and Safety of Prostatic Artery Embolization vs. Transurethral Resection of the Prostate in the Treatment of Benign Prostatic Hyperplasia

Abstract: Background: Prostatic artery embolization (PAE) in the treatment of benign prostatic hyperplasia (BPH) has been introduced into clinical practice, but conclusive evidence of efficacy and safety has been lacking.Objective: To compare the efficacy and safety of prostatic artery embolization (PAE) vs. transurethral resection of prostate (TURP), we performed a meta-analysis of clinical trials.Methods: We searched randomized controlled trials (RCTs) from Pubmed, Embase, Wanfang, and CNKI from January 2000 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In a systematic review and meta-analysis exclusively of randomized controlled trials, Xu et al demonstrated that while prostate volume and Qmax improvement were greater following TURP, there were no significant differences in terms of IPSS, QoL, and PVR between PAE and TURP. 28 The complication rate was also comparable between PAE and TURP, but the former resulted in a lower rate of sexual dysfunction. Similarly, a recently published Cochrane review suggests that PAE may provide similar improvement in urological symptoms and QoL compared to TURP, but PAE is associated with less ejaculatory disorders.…”
Section: Discussionmentioning
confidence: 80%
“…In a systematic review and meta-analysis exclusively of randomized controlled trials, Xu et al demonstrated that while prostate volume and Qmax improvement were greater following TURP, there were no significant differences in terms of IPSS, QoL, and PVR between PAE and TURP. 28 The complication rate was also comparable between PAE and TURP, but the former resulted in a lower rate of sexual dysfunction. Similarly, a recently published Cochrane review suggests that PAE may provide similar improvement in urological symptoms and QoL compared to TURP, but PAE is associated with less ejaculatory disorders.…”
Section: Discussionmentioning
confidence: 80%
“…One metaanalysis found no statistically significant difference in the adverse effects between PAE and TURP [OR 0.90; 95%CI: 0.20-4.05]. 41 The evidence for adverse events between HoLEP and TURP has been…”
Section: Discussionmentioning
confidence: 99%
“…The IPSS score improvement can be used to quantify the success or failure of BPH treatment 40 . Prior literature has been variable regarding the efficacy of PAE, TURP and HoLEP on IPSS score outcomes, with some studies reporting non‐inferiority between the PAE‐TURP and HoLEP‐TURP 1,9,33,41 . A recent meta‐analysis reported that the effect size on IPSS score was MD 1.42 (95%CI: −0.92 to 3.75) when PAE and TURP were compared at 12 months [no statistically significant difference between treatments compared] 41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations